Natalizumab Therapy for Multiple Sclerosis - Derfuss, Tobias; Kuhle, Jens; Lindberg, Raija; Kappos, Ludwig (Seminars in Neurology, 2013)
Natalizumab is a monoclonal therapeutic antibody that inhibits migration of lymphocytes into the central nervous system (CNS) by blocking integrins. Several clinical trials have shown an excellent efficacy in the treatment of relapsing remitting multiple sclerosis. This efficacy is also underlined by postmarketing data of patients with a more aggressive disease compared with the clinical trials. Certain patients might even improve during natalizumab treatment. These positive effects have to be balanced against potential adverse events. In this respect, allergic reactions, hematologic abnormalities, melanoma, lymphoma, infections, and most importantly, progressive multifocal leukoencephalopathy (PML) are discussed. A special emphasis is put on the risk stratification algorithm for PML and approaches for PML treatment. Further, patient and disease characteristics are discussed that might prompt the start or cessation of natalizumab. Finally, data on how to continue after stopping natalizumab are summarized.
Keywords: natalizumab; multiple sclerosis; progressive multifocal leukoencephalopathy